Orthogonal cutting of 3D printed multi-material workpiece: numerical investigation of machining forces, stress, and temperature distribution - Ghasemi, Ali; Duggen, Lars; Malekan, Mohammad (International journal of advanced manufacturing technology, 2024)
With the development of 3D metal printers for rapid prototyping and industrial component production, heightened attention was directed towards post-processing operations for achieving precise surface quality and geometrical tolerances for these components. This paper investigated the orthogonal cutting of multi-material 3D printed workpieces using a coated cutting tool through finite element simulation. The workpieces featured different horizontal and vertical arrangements of layers composed of aluminum 7075-T6 alloy (Al), stainless steel 316 low alloy (SS), and Ti6Al4V alloy (Ti). The study explored the impacts of multi-material composition, coating thickness, and the rake angle of the cutting tool on machining forces, stress distribution, temperature distribution, and chip formation geometry. The results revealed a bimodal chip morphology in the machining process of horizontally arranged SS layers combined with other alloys. The SS layer resulted in a relatively uniform chip formation, while layers with two other materials exhibited a serrated chip formation. In contrast, a discontinuous chip formed when combining Al and Ti materials, as well as in the horizontally arranged layers made of Al, SS, and Ti alloys. The cutting force increased by 2.26 times when cutting workpieces with the horizontal arrangement of SS and Al layers compared to those with a single Al material. For the horizontal and vertical arrangement of layers made of Al and SS, von Mises stress values over the edge of the coated cutting tool significantly increased where the tool contacted the SS layer. Additionally, the horizontal arrangement of layers made of Al and SS materials caused the coated cutting tool to exhibit an extensive temperature distribution, with the maximum recorded temperature reaching 1448 °K. Increasing coating thickness led to a decrease in maximum principal stress at the surface of the tool and a rise in temperature at the cutting edge of the insert.